Myeloid decidual dendritic cells and immunoregulation of pregnancy: defective responsiveness to Coxiella burnetii and Brucella abortus - Gorvel, Laurent; Ben Amara, Amira; Ka, Mignane B.; Textoris, Julien; Gorvel, Jean-Pierre; Mege, Jean-Louis (Frontiers in Cellular and Infection Microbiology, 2014)
Dendritic cells (DCs) are a component of the placental immune system, but their role in pregnancy is still poorly understood. Decidual DCs (dDCs) were selected from at-term pregnancy on the basis of CD14 and CD11c expression. A phenotypic analysis revealed that dDCs are characterized by the expression of monocyte-derived DC (moDCs) markers and specific markers such as HLA-G and its ligand ILT4. As demonstrated by whole-genome microarray, dDCs expressed a specific gene program markedly distinct from that of moDCs; it included estrogen- and progesterone-regulated genes and genes encoding immunoregulatory cytokines, which is consistent with the context of foeto-maternal tolerance. A functional analysis of dDCs showed that they were unable to maturate in response to bacterial ligands such as lipopolysaccharide or peptidoglycan, as assessed by the expression of HLA-DR, CD80, CD83 and CD86. When dDCs were incubated with bacteria known for their placenta tropism, Coxiella burnetii and Brucella abortus, they were also unable to maturate and to produce inflammatory cytokines. It is likely that the defective maturation of dDCs and their inability to produce inflammatory cytokines is related to the spontaneous release of IL-10 by these cells. Taken together, these results suggest that dDCs exhibit an immunoregulatory program, which may favor the pathogenicity of C. burnetii or B. abortus.